2022
DOI: 10.3390/jcm11237052
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pulmonary Function Tests in COVID-19 Convalescents Six Months after Infection

Abstract: Background: The aim of the study was to investigate the impact of COVID-19 on the pulmonary function tests (PFT) in COVID-19 convalescents six months after recovery. Additionally, the research question was whether PFT should be performed routinely in post-COVID-19 patients. Methods: A total of 39 patients with a history of COVID-19 6 months prior to the study were included in the study (Group I). Individuals were hospitalized or treated in the outpatients department. The control group (Group II) consisted of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
(42 reference statements)
0
7
0
1
Order By: Relevance
“…Results of all included studies can be found in Table S1 . All studies included a population with a mean or median age between 47 and 66 years and most studies had an equal distribution of males and females.The majority of the studies were conducted in Europe (n = 26) [ [3] , [4] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] ],49,51,56,60,62,65,66,67,69,70,74,76,77,79,80,81,83,84], six were conducted in North America [ [59] , [60] , [61] , [62] , [63] , [64] ], four in South America [ [65] , [66] , [67] , [68] ] and eleven in Asia [ [16] , [17] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] ]. The population of the studies varied between 17 and 1733 with a mean of 177 participants.…”
Section: Resultsmentioning
confidence: 99%
“…Results of all included studies can be found in Table S1 . All studies included a population with a mean or median age between 47 and 66 years and most studies had an equal distribution of males and females.The majority of the studies were conducted in Europe (n = 26) [ [3] , [4] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] ],49,51,56,60,62,65,66,67,69,70,74,76,77,79,80,81,83,84], six were conducted in North America [ [59] , [60] , [61] , [62] , [63] , [64] ], four in South America [ [65] , [66] , [67] , [68] ] and eleven in Asia [ [16] , [17] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] ]. The population of the studies varied between 17 and 1733 with a mean of 177 participants.…”
Section: Resultsmentioning
confidence: 99%
“…According to many scientists, DLCO most often reflects disorders in the respiratory system during Long COVID. It has been confirmed that even one month after discharge from the hospital, a decrease in DLCO is the most common manifestation of pulmonary dysfunction in people who have contracted it [7,28,29,30].…”
Section: огляди літератури / Literature Reviewsmentioning
confidence: 95%
“…The prevalence of pulmonary symptoms is confirmed in other works. K. Guziejko [7] and others indicate that even six months after recovery, 46% of people have a cough, 23% complain of shortness of breath, and 13% have rapid fatigue as the main symptom. According to Jose-Ramon Blanko [8] et al, symptoms of respiratory dysfunction are observed in patients three months, six months and 12 months after acute infection.…”
Section: огляди літератури / Literature Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to recently published studies, the most common symptoms that persist after COVID-19 include general weakness, shortness of breath and cough. Relatively often, patients also report memory and concentration difficulties and palpitations [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%